40Ar/39Ar geochronology, fluid inclusions, and ore‐grade distribution of the Jiawula Ag–Pb–Zn deposit, NE China: Implications for deposit genesis and exploration. (3rd March 2019) - Niu, Si‐Da; Li, Sheng‐Rong; Huizenga, Jan Marten; Santosh, M.; Zhang, De‐Hui; Li, Zeng‐Da
Abstract : The Jiawula Ag–Pb–Zn deposit is located in the northern part of the Great Xing'an Range metallogenic belt within the eastern segment of the Central Asian Orogenic Belt. Here, we report results from muscovite 40 Ar/ 39 Ar geochronology and fluid inclusion study and formulate a vertical projection map of the ore grade in this deposit. The muscovite from the Jiawula deposit yields a plateau age of 133.27 ± 0.66 Ma and a 40 Ar/ 39 Ar isochron age of 131.88 ± 0.83 Ma. The muscovite 40 Ar/ 39 Ar data indicate a discrete second hydrothermal event postdating the mineralization, which we correlate with post‐collisional extension after the subduction direction of the Palaeo‐Pacific Plate changed. Low‐salinity aqueous fluid inclusions in quartz from the Jiawula deposit represent meteoric water or groundwater. Based on the fluid inclusion study, the fluids were trapped during cooling and decompression, which may have resulted in metal precipitation. We envisage that the copper precipitated from a high‐temperature fluid in the southern domain whereas lead, zinc, and silver precipitated at a lower temperature in the north. The spatial distribution of the ore‐forming elements, therefore, reflects the ore fluid migration‐cooling path from the south to north.